2001
DOI: 10.1164/ajrccm.163.2.9912091
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Markers of Asthma Exacerbation during Stepwise Dose Reduction of Inhaled Corticosteroids

Abstract: To determine predictors for failed reduction of inhaled corticosteroids (ICS), in 50 subjects with well-controlled asthma (age 43.7 [18-69]; 22 males) taking a median dose of 1,000 microg ICS/d (100-3,600 microg/d), ICS were halved every 8 wk. Airway hyperresponsiveness (AHR) to a bronchial provocation test (BPT) with histamine was measured at baseline. AHR to BPT with mannitol, spirometry, exhaled nitric oxide (eNO), and, in 31 subjects, sputum inflammatory cells were measured at baseline and at monthly inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
209
2
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(225 citation statements)
references
References 30 publications
6
209
2
8
Order By: Relevance
“…The concept of achieving 'total asthma control' 5 is 6 important for reducing the future risk of exacerbations [6][7][8] . It is therefore 7 imperative that we have robust procedures for accurate diagnosis, measurement 8 of severity, prediction of future risk, along with appropriate personalised 9 treatments to achieve this goal.…”
Section: Mcid Minimum Clinically Important Difference 46mentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of achieving 'total asthma control' 5 is 6 important for reducing the future risk of exacerbations [6][7][8] . It is therefore 7 imperative that we have robust procedures for accurate diagnosis, measurement 8 of severity, prediction of future risk, along with appropriate personalised 9 treatments to achieve this goal.…”
Section: Mcid Minimum Clinically Important Difference 46mentioning
confidence: 99%
“…Sputum and blood 39 eosinophilia in asthma have both been separately shown to predict loss of 40 asthma control and increased exacerbation rates 6,19,20 . This is also true of 41 fractional exhaled nitric oxide (FeNO) levels 21 and airway hyper-responsiveness 42 (AHR) 6 , the latter being largely driven by airway inflammation 22 . It is therefore 43 logical that one might wish to control inflammation over and above simply 44 controlling symptoms and lung function -much like controlling asymptomatic 45 hypertension to prevent subsequent cardiovascular sequelae.…”
mentioning
confidence: 99%
“…These studies also demonstrated that the change in eNO is a better predictor for loss of asthma control than baseline eNO per se. However, Leuppi et al found no increase in eNO during asthma exacerbations as a result of tapering off inhaled corticosteroids (ICS) [126]. This aberrant observation may be due to measuring eNO offline in contrast with online measurements used in other studies.…”
Section: Exhaled No As a Biomarkermentioning
confidence: 98%
“…Jatakanon a montré que le pourcentage d'éosinophiles pré-sents dans l'expectoration est un facteur prédictif d'une perte de contrôle de l'asthme [39] . Dans une autre étude, Leuppi a rapporté qu'un pourcentage d'éosinophiles supérieur au seuil de 6,3 % avait une sensibilité de 90 % et une spécificité de 63 % pour la prédiction d'une perte de contrôle de l'asthme lors du sevrage en corticostéroïdes inhalés [44] . L'inflammation éosinophilique des voies respiratoires qui persiste malgré un traitement antiinflammatoire intensif est associée à un asthme plus sévère [45,46] , des exacerbations plus fréquentes [47] et un déclin de la fonction respiratoire [48] .…”
Section: Intérêt Dans L'évaluation Du Contrôle Et De La Sévérité De Lunclassified
“…De plus, des études de sevrage des corticostéroides [44,59] ont montré que l'éosinophilie de l'expectoration augmente avant l'apparition de l'exacerbation, suggérant que le traitement ciblé par corticostéroïdes inhalés à visée de normalisation du pourcentage d'éosinophiles présents dans le sputum pourrait conduire à une réduction du nombre d'exacerbation chez l'asthmatique. Dans un essai contrôlé randomisé [47] incluant 74 asthmatiques, les patients bénéficiant du traitement adapté en vue de normaliser l'éosinophilie de l'expectoration ont montré un nombre significativement plus faible d'exacerbations sévères et d'hospitalisations que les patients dont le traitement était adapté en fonction des recommandations standard.…”
Section: Intérêt Dans L'ajustement Du Traitement Anti-inflammatoire Eunclassified